Quantitative description of atomic architecture in solid solutions: A generalized theory for multicomponent short-range order - Ceguerra, A; Powles, R; Moody, M; Ringer, S (2010)
This Brief Report introduces a short-range order parameter, called the generalized multicomponent short-range order (GM-SRO) parameter. The application to Monte Carlo simulations is described for higher order solid solutions. The results show the ability to create atomic-scale systems with a particular subset of the GM-SRO parameters and the power of the GM-SRO expressions in determining the relationship between two sets of atomic species. © 2010 The American Physical Society.